Multiple metastases from ovarian cancer - Daleep Singh; Shankar Jakhar; Puneet Bagri; Akhil Kapoor; H Kumar (South African Medical Association, 2014)
Epithelial ovarian cancer is one of the most common ovarian tumours. Ovarian cancer affects women in the age group >60 years much more frequently than younger women. At the time of diagnosis, cancer will already have spread beyond the ovaries in approximately 75% of cases. We report a case of epithelial ovarian cancer presenting with liver and thoracic vertebral metastases 4 months after completion of treatment, as part of distant spread. The patient was then treated with gemcitabine-based chemotherapy. Palliative radiotherapy was given for the involved spine.